Evaluation of an Aspergillus IgG/IgM lateral flow assay for serodiagnosis of fungal asthma in Uganda. - Richard Kwizera (Public Library of Science (PLoS), 2021)
Background Diagnosis of fungal allergies in asthma remains problematic in low-and middle-income countries due to non-availability of point-of-care testing. In this study, we aimed to evaluate the performance of an Aspergillus immunochromatographic technology (ICT) IgG/M lateral flow device (LFD) for the serological diagnosis of allergic bronchopulmonary aspergillosis (ABPA) and severe asthma with fungal sensitisation (SAFS) among Ugandan adult asthmatics. Methods 374 adult (aged ≥18years) asthmatics in the African Severe Asthma Program study, Ugandan site constituted the study population. ABPA and SAFS were diagnosed according to standard criteria. Asthmatics who did not meet the above criteria constituted a control group. The LFD tests were performed and read according to manufacturer's instructions. Results ABPA was found in 12/374 (3.2%) and SAFS in 60/374 (16%) participants. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) for the Aspergillus ICT for the diagnosis of ABPA were 0.0%, 96.4%, 0.0% and 96.7% respectively, and for SAFS 6.7%, 97.1%, 30.8% and 84.5% respectively. False positive and negative rates were 3.5% and 3.2% for ABPA and 2.4% and 14.9% for SAFS, respectively. Patients with a positive LFD significantly had higher median Aspergillus fumigatus-specific IgE levels compared to those with negative LFD (median: 0.06 kUA/l VS 0.03 kUA/L, P = 0.011). Conclusion The Aspergillus ICT IgG/M LFD had a poor diagnostic performance for the diagnosis of both ABPA and SAFS. Its greatest value may be in distinguishing chronic and allergic aspergillosis in Africa.